2001
DOI: 10.1021/ac0117613
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Kinetically Monovalent Binding Affinity by Immunoassays Based on Multivalent Nanoparticle−Antibody Bioconjugates

Abstract: Page 2256, last paragraph, last sentence, should read, "The slope represented the dissociation rate constant of pure dissociation phase reaction, based on an integrated form of the rate 39 where R 0 was a response at t ) 0 and R n a response at t ) n."Page 2257, Table 1, headings of third and fourth columns should read "association rate const, k a (M -1 s -1 /1 × 10 5 ) a,c " and "dissociation rate const, k d (s -1 /1 × 10 -5 ) a ", respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
41
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 0 publications
1
41
0
Order By: Relevance
“…Thus, proper monitoring of total PSA levels (other than through biopsy) is critical for the evaluation of the prostate cancer malignancy. Enzyme linked immunosorbent assays (ELISAs), uorescence immunoassays, 6 chemiluminescent assays, 7 and time-resolved immunouorometric assays 8,9 have been developed for PSA detection. ELISA is quite a promising technique but it is time consuming, requires labeling and is not sufficient for sensitive detection if the biomarker is present in very low concentrations (sub nanogram to picogram levels).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, proper monitoring of total PSA levels (other than through biopsy) is critical for the evaluation of the prostate cancer malignancy. Enzyme linked immunosorbent assays (ELISAs), uorescence immunoassays, 6 chemiluminescent assays, 7 and time-resolved immunouorometric assays 8,9 have been developed for PSA detection. ELISA is quite a promising technique but it is time consuming, requires labeling and is not sufficient for sensitive detection if the biomarker is present in very low concentrations (sub nanogram to picogram levels).…”
Section: Introductionmentioning
confidence: 99%
“…Some types of immunoassay for PSA have been reported, such as fluorescence microscopy, surface plasmon resonance technology, lateral flow immunoassay, enzyme-linked immunosorbent assay (ELISA), radioimmunoassay, immunochromatographic assay system, and SERS based on immunoassays. [15][16][17]26,[37][38][39][40][41][42][43][44] In this study, we applied a sandwich type SERS immunoassay for the detection of PSA with high sensitivity. It shows the possible application of SERS immunoassay with monoclonal antibodies that is sensitive enough for analysis of PSA in human blood samples or cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this technique is considerably favorable for bioassays using nanoparticles as the luminescence probe if only the nanoparticle probe has a luminescence lifetime long enough for time-resolved luminescence measurement. On the other hand, the TR-FIAs using fluorescent lanthanide chelate conjugated macromolecules, such as polyvinylamine [13][14][15], poly(Glu:Lys)-streptavidin conjugate [16], and polystyrene latex particles [17][18][19][20][21], as the fluorescence probes have shown that the sensitivity of TR-FIA can be remarkably improved since the fluorescence intensities of the macromolecule probes have been enhanced by attaching many fluorescent lanthanide molecules to the macromolecule probes.…”
Section: Introductionmentioning
confidence: 99%